19. Yüzyıl Türk Aydınında Voltaire İlgisi / Interest of Voltaire on the Turkish Intellectuals of the 19th Century - Tural, Secaattin (Journal of History Culture and Art Research, 2014)
Öz Voltaire, gerek Avrupa’da meydana gelen Aydınlanma hareketinin, gerekse Fransız İhtilalinin düşünsel hazırlayıcılarından biri olmasıyla öne çıkan bir isimdir. Onun felsefeci kimliği yanında edebi sahada da ürünler vermesi ve buna ek olarak mücadeleci kişiliği Aydınlanma dönemi Avrupa’sının önemli aktörlerinden biri olmasını sağlamıştır. Dolayısıyla Batılılaşma maceramızda aydınlarımızın onunla tanışması kaçınılmaz olmuştur. Tanzimat sonrası gelişen Türk edebiyatı aynı zamanda Batılılaşma maceramızı da içerdiğinden dönemin aydınları, Batı ile kurdukları ilişkide genellikle hep bu akılcı ve ihtilalci düşünce adamlarına ilgi duymuştur. Bu ilgi öncelikle çeviriler yoluyla kendini göstermiş, sonrasında ise onların düşünceleri yazarlarımızın ana temalarından biri haline gelmeye başlamıştır. Biz de bu makalede söz konusu Aydınlanma filozoflarından biri olan Voltaire’in Batılılaşma hareketinin öncüsü sayılabilecek Türk edebiyatı üzerindeki etkisi üzerinde durmaya çalıştığımızda gördük ki Münif Paşa, Beşir Fuad başta olmak üzere Batılılaşma hareketimizde önemli sayılabilecek isimler Voltaire’den hayli etkilenmişlerdir. Abstract Voltaire is a philosopher who stands out as one of the ideological predecessors who paved the way not only for the Enlightenment Period in Europe, but also for the French Revolution. His literary products apart from his identity as a philosopher as well as his assertive character as a struggler led him to be one of the leading actors in Europe during the Enlightenment Period. Therefore, it has been unavoidable for Turkish intellectuals to meet this strong figure throughout our westernization experience. Since the post-Tanzimat period Turkish literature also involves our westernization process, the Turkish intellectuals of the era identified themselves with such rationalist and revolutionist thinkers. The interest in these prominent thinkers was first revealed through translations and then it turned out to be one of the major themes favoured by Turkish authors. As we started to search for this article into the effect of Voltaire on Turkish literature which led and triggered Turkish westernization, we discovered that pioneers of Turkish westernization movement especially Münif Pasha and Besir Fuad had been deeply inspired by Voltaire.